Answer:
The answer is B. (-7,-2)
Step-by-step explanation:
Multiply the first equation by 7,and multiply the second equation by -6.
7(−3x+6y=9)
−6(5x+7y=−49)
Becomes:
−21x+42y=63
−30x−42y=294
Add these equations to eliminate y:
−51x=357
Then solve−51x=357for x:
−51x=357 Divide both sides by -51
x=-7
Write down an original equation:
−3x+6y=9
Substitute−7forxin−3x+6y=9:
(−3)(−7)+6y=9
6y+21=9(Simplify both sides of the equation)
6y+21+−21=9+−21(Add -21 to both sides)
6y=−12
y=-2
Step-by-step explanation:
1/2(4-14y)=y+50
1/(8 - 28y) = y + 50
8y - 400 - 28y² +
Now you can solve
Two correct answers:
9 + x
x + 9
Or you can say
x - -9
or
9 - -x
Answer:
y=6x+20
Step-by-step explanation:
x=3 1/4 is not a solution to the equation.
12 5/8=x+9 1/4 Subtract 9 1/4 from each side 3 3/8=x, but 3 1/4=3 2/8